The Practice of Implementing Project-Based Learning in the EFL Classroom - Irén Nagy (GiLE Journal of Skills Development)
This literature review focuses on the use and effectiveness of Project-Based Learning in teaching English as a foreign language and its significance in developing students’ English language skills and 21st century skills, with special focus on critical thinking, cooperation and digital skills, which are essential skills for young people entering the workforce in the 21st century. The review was based on short-term and long-term projects with upper secondary school students and university students, applying both qualitative and quantitative data collection methods and aims to identify the advantages and challenges teachers and students face during the implementation of PBL and its effectiveness in developing students’ skills. The review reveals that PBL can be an effective method in developing both students’ English language skills and 21st century skills, the main advantage being facilitating student engagement by allowing them to make their own choices. Another important finding is that using PBL in the classroom may be challenging for both teachers and students due to the amount of time preparation and implementation requires and the lack of training teachers receive.